2017
DOI: 10.1007/s13204-017-0611-x
|View full text |Cite
|
Sign up to set email alerts
|

Fabricated CeO2 nanopowders as a novel sensing platform for advanced forensic, electrochemical and photocatalytic applications

Abstract: In Forensic investigation, identification of various types of ridge details are essential in order to fix the criminals associated in various crimes. Even though several methods and labeling agents are available to visualize latent finger prints (LFPs) there is still simple, accurate, cost-effective, and non-destructive tool is required. In the present work, CeO 2 nanopowders (NPs) are prepared via simple solution combustion route using Tamarindus indica fruit extract as a fuel. The optimized NPs are utilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Point of care diagnostic studies have been reported with the use of mobile phone-based SPCE platform for picomolar sensing of Lipoprotein-Associated Phospholipase A 2 (LpPLA 2 ) coronary heart disease biomarker and realizing 10 nM limit of detection of tryptophan using CIE chromaticity diagram. These CIE coordinates have been extensively used for analysis and understanding of physicochemical, optical and thermal interactions in various systems involving (a) comparison of emission of tricomponent micelle cocktail before and after UV irradiation, (b) estimation of correlated color temperature (CCT) using photoluminescence (PL) emission spectra of as-formed and calcined samples, (c) detection of organic amines in vapors using bright red–light purple emission corresponding to basic–acidic environments, and (d) energy transfer caused by codoping of inorganic phosphors and resultant change in emission wavelengths . Moreover, CIE color space has been utilized for distinguishing spacer, cavity and extended cavity nanointerfaces in plasmon-coupled emission platforms as detailed in our earlier works. , In brief, according to the Commission Internationale de I’Eclairge 1931 color space, the color matching function of the human eye is defined by xyY values.…”
Section: Resultsmentioning
confidence: 99%
“…Point of care diagnostic studies have been reported with the use of mobile phone-based SPCE platform for picomolar sensing of Lipoprotein-Associated Phospholipase A 2 (LpPLA 2 ) coronary heart disease biomarker and realizing 10 nM limit of detection of tryptophan using CIE chromaticity diagram. These CIE coordinates have been extensively used for analysis and understanding of physicochemical, optical and thermal interactions in various systems involving (a) comparison of emission of tricomponent micelle cocktail before and after UV irradiation, (b) estimation of correlated color temperature (CCT) using photoluminescence (PL) emission spectra of as-formed and calcined samples, (c) detection of organic amines in vapors using bright red–light purple emission corresponding to basic–acidic environments, and (d) energy transfer caused by codoping of inorganic phosphors and resultant change in emission wavelengths . Moreover, CIE color space has been utilized for distinguishing spacer, cavity and extended cavity nanointerfaces in plasmon-coupled emission platforms as detailed in our earlier works. , In brief, according to the Commission Internationale de I’Eclairge 1931 color space, the color matching function of the human eye is defined by xyY values.…”
Section: Resultsmentioning
confidence: 99%
“…This data conrmed that the surface conned species resulted in a redox peak current. 93 Nanoceria can neutralize free radical chemical species by undergoing redox changes (Ce 3+ 4 Ce 4+ ). Based on this characteristic, cyclic voltammetry (CV) and chronoamperometry responses of multi-valent nanoceria on the GCE in presence of H 2 O 2 was developed as an enzyme-free nanoceria-based sensor.…”
Section: Electrochemical Sensormentioning
confidence: 99%
“…Various traditional systems, such as electrochemical oxidation, membrane filtration, adsorption, chlorination, reverse osmosis, and photocatalysis, have been agreed to treat the harmful dyes covering wastewater. Amid these skills, semiconductors (SCs) based photocatalysis has drawn increasing interest because it offers a capable substitute strategy to eradicate the dye-containing wastewater since of its high efficacy, green reaction route and moderate reaction settings (Rohini et al 2017) for solving the recent severe problems of environmental pollution and energy shortages. Unfortunately, the utmost of these physical, chemical and biological systems could custom to secondary impurities simply through degradation manners (Venkatasubramanian et al 2008).…”
Section: Introductionmentioning
confidence: 99%